UPDATE ON GAME HARD-SURFACE MODELLING - Mohammad Fadly, S.E, M.M, Mohammad Fadly, S.E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
While the modern game production cycle has high expectations for artistic and technical solutions, it has little room for iterations and fixes. Artists are taking novel methods to routine activities in order to streamline the production flow and improve the quality of the 3D models. The purpose of this thesis was to document and describe the technological process followed when making high-poly, hard-surface assets for a video game. This study details the modelling pipeline in Autodesk's Fusion 360, as well as the general and hard-surface specific design ideas an artist could employ to produce a realistic weapon model. This thesis demonstrates the development of a concept and a high-poly model of a pistol in accordance with requirements using a practical approach and design theory. The benefits and adaptability of Fusion 360 were discussed, as were the author's personal experiences with the modelling process, tools, and bestpractises. In conclusion, the thesis summarises the outcomes of the modelling and identifies the primary advantages of the Fusion 360 and demonstrates the workflow utilised to generate a highpoly model of a pistol. The author of this study has created the pipeline necessary to effectively tackle a wide range of hard-surface modelling jobs for AAA video games.